Resistance to Thrips in Peanut and Implications for Management of Thrips and Thrips-Transmitted Orthotospoviruses in Peanut - Srinivasan, Rajagopalbabu; Abney, Mark R.; Lai, Pin-Chu; Culbreath, Albert K.; Tallury, Shyam; Leal-Bertioli, Soraya C. M. (Frontiers in Plant Science, 2018)
Tobacco thrips, Frankliniella fusca (Hinds), is a major pest of peanut (Arachis hypogaea L.) in the southeastern United States, and is a vector of an Orthotospovirus, Tomato spotted wilt virus (TSWV). Host plant resistance to thrips could be pivotal in reducing feeding damage and preventing virus transmission. A tremendous effort has been devoted to developing peanut cultivars with resistance to pathogens including TSWV and nematodes. However, not much is known about host resistance to thrips. Until recently, research on thrips-host interactions was limited to field evaluations of feeding damage. Over the last few years, laboratory studies have revealed that peanut cultivars could differentially affect thrips feeding and thrips biology. Many runner type cultivars, partially resistant to TSWV, representing diverse pedigrees were evaluated against thrips. Feeding damage evaluations over a 30-day period were done in the greenhouse under choice and no-choice settings. Results revealed that thrips preferred some cultivars over others under choice settings. In other crops, morphological traits such as leaf architecture and waxiness and spectral reflectance have been associated with thrips non-preference. It is possible that foliar morphological traits in peanut could be associated with reduced preference of thrips, and that antixenosis could be responsible for thrips resistance. Spectral reflectance differs among peanut cultivars, but its involvement in thrips host preference or non-preference needs to be examined in depth. Numerous no-choice experiments were conducted to examine the effects of cultivars on thrips life history traits. Thrips larval survival to adulthood and median developmental time were negatively affected in some cultivars, suggesting that antibiosis could be involved as well. Similar results were obtained from studies on thrips life history traits with a diploid peanut species, Arachis diogoi (Hoehne), and its hybrids with a Virginia type cultivar. Together these results suggest that there could be antixenosis and antibiosis factors in peanut cultivars/genotypes negatively impacting thrips. TSWV transmission was also somewhat reduced in those cultivars with thrips resistance. Cultivars with thrips and TSWV resistance would be better suited to limit thrips and virus-induced losses in peanut.